2014
DOI: 10.4314/star.v3i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Forest Carbon Stocks in Woody Plants of Mount Zequalla Monastery and It’s Variation along Altitudinal Gradient: Implication of Managing Forests for Climate Change Mitigation

Abstract: Article InformationCarbon sequestration through forestry has the potential to play a significant role in ameliorating global environmental problems such as atmospheric accumulation of GHG's and climate change.The present study was undertaken to estimate forest carbon stock along altitudinal gradient in Mount Zequalla Monastery forest. Systematic sampling methods were used to collect data from seventy 10 m x 20 m rectangular plots. The area was dominated by Juniperusprocera tree species. The mean carbon stock p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 36 publications
(29 reference statements)
3
10
1
Order By: Relevance
“…However, it was found to be above one-fold of the reported value of Sub-Saharan Africa above ground biomass carbon (321.29 t ha -1 ). According to the total carbon, the current study result was relatively greater than that of some of the reported carbon stock studies of Ethiopian forests; Mount Zequalla forest (Girma et al, 2014) and Humbo forest (Chinasho et al, 2015) (Table 7). However, the present result is smaller to that of Egdu forest (Yohannes et al, 2015) and Tara Gedam forest (Gedefaw, 2015) ( Table 7).…”
Section: Carbon Stored In Each Individual Plant Speciescontrasting
confidence: 79%
See 2 more Smart Citations
“…However, it was found to be above one-fold of the reported value of Sub-Saharan Africa above ground biomass carbon (321.29 t ha -1 ). According to the total carbon, the current study result was relatively greater than that of some of the reported carbon stock studies of Ethiopian forests; Mount Zequalla forest (Girma et al, 2014) and Humbo forest (Chinasho et al, 2015) (Table 7). However, the present result is smaller to that of Egdu forest (Yohannes et al, 2015) and Tara Gedam forest (Gedefaw, 2015) ( Table 7).…”
Section: Carbon Stored In Each Individual Plant Speciescontrasting
confidence: 79%
“…Estimating of Litter, Herbs and Grass Biomass: The litter layer includes dead leaves, twigs, dead grasses, and small branches, fragments of organic material and dead wood with a diameter of less than 10 cm (Girma et al, 2014). Biomass carbon stock was estimated from sub-samples taken in the field.…”
Section: Carbon Stock Biomass Estimation For Different Carbon Poolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekele-Mariam forest is one of the dry Afromontane forest in West Gojjam Zone North-Western Ethiopia and its carbon stock potential is not studied yet. Altitude is one of the key environmental factor that had significant impact on carbon pools (aboveground, belowground, litter and soil) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The quadrat size of 10 m × 10 m was used to collect data for tree biomass following the guidelines given by Savilaakso et al [22]. Similarly, others used [23][24][25][26][27][28], trees on the border were only included if more than 50% of their basal area falls within the plot. Trees overhanging in to the plot were excluded, but trees with their trunk inside the sampling plot and branches outside were included.…”
Section: Data Collection (Vegetation Data Collection and Identification)mentioning
confidence: 99%